The promises and pitfalls of universal early education - Elizabeth Cascio (IZA World of Labor, 2015)
There is widespread interest in universal early education, both to promote child development and to support maternal employment. Positive long-term findings from small-scale early education interventions for low-income children in the US have greatly influenced the public discussion. However, such findings may be of limited value for policymakers considering larger-scale, more widely accessible programs. Instead, the best insight into the potential impacts of universal early education comes from analysis of these programs themselves, operating at scale. This growing research base suggests that universal early education can benefit both children and families, but quality matters.
Keywords: I2; H2; J2; 330; early education; preschool; childcare; universal early education